Performance and carcass yield of female broilers fed with diets containing probiotics and symbiotics as an alternative to growth enhancers (Acta Scientiarum. Animal Sciences, 2018)
An experiment was carried out with female broilers, aiming to evaluate the effect of using probiotics and symbiotics on growth performance and yield of carcasses and of the main commercial cuts and edible viscera. A total of 720 one-day-old Cobb chicks, distributed in a completely randomized experimental design with four treatments and six replicates of 30 birds each at a stocking density of 10 birds per square meter (m2). At 42 days old two broilers of each experimental unit were sacrificed to evaluate the carcass yield and its parts. The carcass yield was not affected by the inclusion of probiotics and symbiotics in the diet being equivalent to the antibiotic group. No significant difference was observed among the treatments, even in the controls that did not receive any additive factor. All the performance parameters were similar for the four treatments, with the exception of weight gain, that was significantly lower in probiotic treatment. It was concluded that these additives are important alternative to replace antibiotics as growth enhancers, which have already been banned in many countries.